SMART MEDICINE REMINDER AND MONITORING USING ARDUINO - Asha S.Gadhave1,Nilesh Pandhare2, Rupali T. Bansode 3, Sanjeevani S. Bhinge 4 (International Journal of Innovations in Engineering Research and Technology, 2022)
Arduino is providing the means by which it is possible to collect and analyze data remotely without any human interaction. So, this indicates that it is possible to detect and prevent any future hazard with precision and possible to aware the concerning authority like the family member or the physician if there is any alarming situation.The core to our motivation was to think ahead of our time and to make a contribution on the sector Arduino which is undoubtedly the next big thing on the technological market. And Arduino has proven itself to be a very handy possession. The idea of this project came to us by observing how easy it is to connect or integrate the normal home appliances with the internet. This led us to the secluded health sector which is still lagging behind from other industries in terms of technology. We observed many case even from our daily lives that in the hectic world we are living right now, it is difficult to keep a watch over everything. Specially, to keep an eye on the elderly people is difficult and costly as well. These real life situations gave us the ideas and motivation to integrate the two sectors so that it helps in developing such a project which will create an economic and efficient health monitoring system and will pave the way for future work on the field of Arduino. In taking of genuine estimation at proper time is an obligatory things of every patents on the planet .The patients may incorporate kids, understudies businessperson and matured people .If they would encounter the evil impact of any affections or sickness, by then it is critical to take their correct portions gainfully, especially senior resident, relatives are the person who should help the patients however because of this distinctive issue emerge, for example, taking unpredictable medications because of patients bustling calendar and absence of information about the drug .By then it is essential to take best possible prescriptions for their extraordinary prosperity. In modern society, busy life has made people forget many things in day to day life. The elderly people and the people victims of chronicle diseases who need to take the medicines timely without missing are suffering from dementia, which is forgetting their daily routine. It can overcome by development of a low cost medical sensing, communication and analytics device that is real time monitoring allowed patients physical conditions. As the expense of the in-home restorative consideration rises, every individual search for a productive contraption to manage their medications fittingly. Despite the fact that there are diverse medication remnants it has been hard to work by elderly individuals. To maintain a strategic distance from such circumstances brilliant drug leftover portion is produced to assist the patients with taking appropriate measurements adequately. The fundamental preferred standpoint of this framework is that elderly individuals can work this framework effortlessly. The basic two reasons Arduino is important for this project is firstly it is automated, so no human interaction is needed. And secondly, because of automation the process has less chance of having errors i.e. having a more efficient system indicating a better quality in service.